(untitled) (Research, Society and Development, 2025)
This article is part of a master’s dissertation currently being developed within the Professional Master’s Program in Professional and Technological Education (PROFEPT) at the Farroupilha Federal Institute (IFFar), Jaguari/RS campus. It’s linked to the GECPOL Research Group at IFFar. The article aims to present an analysis of scientific publications addressing the integration of Computing in Basic Education, emphasizing discussions regarding its application in Professional and Technological Education, based on research conducted within stricto sensu graduate programs. The methodology used follows the State-of-the-Art approach, according to authors such as Medeiros, Romanowski and Santos, through a mapping of academic outputs on the topic. The investigation revealed various approaches to addressing the theme, highlighting, among the analyzed works, the titles "Computational Thinking in High School Mathematics: A Pedagogical Proposal for the Study of Functions" and "Computer Science in Education: Redefining Curricula and Teaching Methods." The former focuses on the practical application of computational thinking in the classroom, while the latter discusses guidelines and public policies aimed at integrating computer science into education. In addition to these works, other studies were mapped, revealing the contexts of application, target audiences, and methodologies adopted, thus contributing to a broad and critical view of the current landscape of Computing in Basic Education.